The Abuse of Power by “Indonesian Leaders” - Nuah Perdamenta Tarigan (Bina Nusantara University, 2016)
Indonesian leadership for some time suffered extraordinary shocks, the distrust of the leaders to make them not a role model anymore. The loss of integrity within the leader is very worrying for our state and nation; Indonesia's national security can be destroyed by it. It takes a very drastic change in the future to build Indonesia. Strong faith basis and professionalism coupled with a good work ethic will bring this nation to obtain a real leader, not worthy of their so-called leaders. Abuse of power that has been handed over to the leaders of the people are already too many and has touched every joint life of Indonesian society, there needs to be a consistent transformation of the nation's future, otherwise we will be destroyed, and the free fall in the abyss of evil. This paper will describe the current situation of Indonesia as well as concise and clear feedback about the solution, hopefully this can be determined for all of us to rebuild Indonesia.